2010
DOI: 10.1017/cbo9780511762895
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Strategy

Abstract: Is there a 'Western way of war' which pursues battles of annihilation and single-minded military victory? Is warfare on a path to ever greater destructive force? This magisterial 2010 account answers these questions by tracing the history of Western thinking about strategy - the employment of military force as a political instrument - from antiquity to the present day. Assessing sources from Vegetius to contemporary America, and with a particular focus on strategy since the Napoleonic Wars, Beatrice Heuser exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(4 citation statements)
references
References 155 publications
0
4
0
Order By: Relevance
“…Later still, war would transform in the Nuclear Age, when the "total war" construct required new modes of deterrence to ensure species survival. 43 This transformation was first proposed by James E. King Jr. and developed by U.S. Navy rear admiral Henry E. Eccles, an influential Naval War College professor and strategist in the 1940s through 1970s. 44 Examining the rise of nuclear peer adversaries between the United States and the Soviet Union in what became defined as the Cold War, King and Eccles suggested that all conflict prior to the late 1940s had no artificial stopping point or existential deterrence factor, so concepts such as Clausewitzian "absolute war" ideal could be sought in any conflict by either side, such as the runaway offensive strategies that eventually bled European nations white in World War I.…”
Section: This Paradigmmentioning
confidence: 99%
See 2 more Smart Citations
“…Later still, war would transform in the Nuclear Age, when the "total war" construct required new modes of deterrence to ensure species survival. 43 This transformation was first proposed by James E. King Jr. and developed by U.S. Navy rear admiral Henry E. Eccles, an influential Naval War College professor and strategist in the 1940s through 1970s. 44 Examining the rise of nuclear peer adversaries between the United States and the Soviet Union in what became defined as the Cold War, King and Eccles suggested that all conflict prior to the late 1940s had no artificial stopping point or existential deterrence factor, so concepts such as Clausewitzian "absolute war" ideal could be sought in any conflict by either side, such as the runaway offensive strategies that eventually bled European nations white in World War I.…”
Section: This Paradigmmentioning
confidence: 99%
“…79 This nuanced with Jomini and his more rigid analysis that all war could be reduced into general principles and rules for the clever leader to outwit and defeat opponents with. 80 However, for Clausewitz, Jomini, and their contemporaries studying war in the wake of the Napoleonic era, the "ideal" war is a pure, total, and perfect manifestation, while due to the fog and friction of human behaviors both collectively and individually within an ever-changing world, only the "real" wars might materialize. 81 Real war spanned from nations suppressing insurrections and insurgencies to that of near-total state warfare that would be demonstrated with increasing devastation in the two world wars of the twentieth century.…”
Section: Phantasmal Warsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a depiction of the universal and eternal features of strategy-making. Strategy, as a term we would understand today, was first utilized in 1770s 6 , however, as Gray noted, the basic logic of strategy is to be found in all places and periods of human history, regardless of which term was used by distinct societies or cultures. Strategy is unavoidable because human, the common denominator between the past and the future, always needs security and it is in his/her nature to behave politically and strategically against potential dangers.…”
Section: Strategy and Strategic Theorymentioning
confidence: 99%